Repair of Full-Thickness Defects in Alimentary Tract Wall With Patches of Expanded Polytetrafluoroethylene - Oh, Daniel S. (2002)
OBJECTIVES: To test the efficacy of patches of expanded polytetrafluoroethylene (ePTFE) for the repair of full-thickness defects in alimentary tract wall. SUMMARY BACKGROUND DATA: A recent report of successful replacement of duodenal wall with patches of ePTFE was met with skepticism and clearly warranted confirmation as well as evaluation in repair of other segments of the abdominal intestinal tract. METHODS: Defects of 4 cm(2) were created in various segments of canine abdominal alimentary tract (stomach, duodenum, small bowel, and colon) as well as in bladder dome. For the duodenum in 13 dogs, three different ePTFE fabrications were used: CVX (cardiovascular), PDX (preclude dura membrane), and DLM (dual mesh plus). In repair of the other areas in six dogs, the PDX patch was used. When the animals were killed, both gross inspection of the parietes and tissue for histologic study became the basis for evaluation. Peritoneal and intraluminal cultures of the specific study viscera were also taken. RESULTS: There were no patch failures. Only six significant adhesions were noted in 3 of the 19 dogs. Serosal surface healing was complete without exception by 1 week in all animals. Patches of CVX and PDX had heaping mucosa at the margin of well-sealed patch edges in the study involving duodenum. However, the DLM patch had an undergrowth of mucosa with partial patch separation by 1 week, beginning patch extrusion into gut lumen at 3 weeks, and total separation of patch with complete mucosal repair at 6 weeks. The fate of the PDX patches at 6 weeks in stomach, small bowel, colon, and bladder was identical to what had been observed for the PDX patch in the duodenum. All peritoneal and bladder cultures had no growth, whereas the contents of the alimentary tract grew expected flora. CONCLUSIONS: These observations suggest that ePTFE may well be an acceptable membrane for at least temporary replacement of full-thickness hollow viscus defects, even in the face of heavy bacterial contamination, and that certain structural configurations of ePTFE may provide a base for increasing absorptive mucosal surface area.